ROLE OF NATIONAL VALUES IN THE INCREASING PATRIOTIC FEELINGS IN THE HEARTS OF YOUNG PEOPLE (Scientific journal of the Fergana State University, 2026)
This article highlights the urgent tasks of preserving the spirituality and consciousness of the younger generation, educating them in the spirit of national and universal values, and forming mature personnel capable of expressing their independent opinion on the events happening around them, deeply understanding the meaning and true causes of the political processes taking place in the world.